Automobile injury trends in the contemporary fleet: Belted occupants in frontal collisions. (18th August 2019) - Forman, Jason; Poplin, Gerald S.; Shaw, C. Greg; McMurry, Timothy L.; Schmidt, Kristin; Ash, Joseph; Sunnevang, Cecilia
Abstract: Objective: As vehicle safety technologies and evaluation procedures advance, it is pertinent to periodically evaluate injury trends to identify continuing and emerging priorities for intervention. This study examined detailed injury distributions and injury risk trends in belted occupants in frontal automobile collisions (10 o'clock to 2 o'clock) using NASS-CDS (1998–2015). Methods: Injury distributions were examined by occupant age and vehicle model year (stratified at pre- and post-2009). Logistic regression models were developed to examine the effects of various factors on injury risk (by body region), controlling for delta-V, sex, age, height, body mass index (BMI), vehicle model year (again stratified at 2009). Results: Among other observations, these analyses indicate that newer model year vehicles (model year [MY] 2009 and later) carry less risk of Abbreviated Injury Scale (AIS) 2+ and AIS 3+ injury compared to older model year vehicles, with odds ratios of 0.69 (AIS 2+) and 0.45 (AIS 3+). The largest reductions in risk between newer model year vehicles and older model year vehicles occur in the lower extremities and in the risk of skull fracture. There is no statistically significant change in risk of AIS 3+ rib fracture or sternum injury between model year categories. Females are at greater risk of AIS 2+ and AIS 3+ injury compared to males, with increased risk across most injury types. Conclusions: For belted occupants in frontal collisions, substantial reductions in injury risk have been realized in many body regions in recent years. Risk reduction in the thorax has lagged other body regions, resulting in increasing prevalence among skeletal injuries in newer model year vehicles (especially in the elderly). Injuries also remain common in the arm and hand/wrist for all age ranges studied. These results provide insight into where advances in the field have made gains in occupant protection and what injury types remain to be addressed.